Psychiatric symptoms in preclinical behavioural-variant frontotemporal dementia in MAPT mutation carriers. Issue 5 (20th January 2018) - Cheran, Gayathri; Silverman, Hannah; Manoochehri, Masood; Goldman, Jill; Lee, Seonjoo; Wu, Liwen; Cines, Sarah; Fallon, Emer; Kelly, Brendan Desmond; Olszewska, Diana Angelika; Heidebrink, Judith; Shair, Sarah; et al.
Abstract : Objective: To characterise psychiatric symptoms in preclinical and early behavioural-variant frontotemporal dementia (bvFTD), a neurodegenerative disorder whose symptoms overlap with and are often mistaken for psychiatric illness. Methods: The present study reports findings from a systematic, global, prospective evaluation of psychiatric symptoms in 12 preclinical carriers of pathogenic MAPT mutations, not yet meeting bvFTD diagnostic criteria, and 46 familial non-carrier controls. Current psychiatric symptoms, informant-reported symptoms and lifetime prevalence of psychiatric disorders were assessed with The Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) and the Neuropsychiatric Inventory Questionnaire. Fisher exact test was used to compare carriers and non-carriers' lifetime prevalence of six DSM-IV disorders: major depressive disorder, panic attacks, alcohol abuse, generalised anxiety disorder, panic disorder, and depressive disorder not otherwise specified. Other DSM-IV disorders had insufficient prevalence across our sample for between-group comparisons, but are reported. Results: Non-carriers had greater prevalence of mood and anxiety disorders than has been reported for a general reference population. Preclinical carriers had lower lifetime prevalence of mood and anxiety disorders than non-carriers, except for depressive disorder not otherwise specified, an atypical syndrome comprising clinically significant depressive symptoms which fail to meet criteria for major depressive disorder. Conclusion: Findings suggest that early psychiatric symptoms of emergent bvFTD may manifest as emotional blunting or mood changes not cleanly conforming to criteria for a DSM-defined mood disorder.